Phraseology and phraseological combinations in linguistics - Atamirzayeva Makhliyo Habibullayevna (Zien Journals, 2023)
One of the departments of linguistics is the department of phraseology. This department provides information about the phrasemes in the vocabulary of the language. A linguistic unit consisting of the combination of more than one independent lexeme, which has a figurative and spiritual nature, is called a phraseology: "The hair on the top stood on end, the vinegar does not hold water, etc."
Keywords: Phraseological combinations; unity; phraseology